2006
DOI: 10.1515/cclm.2006.067
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter evaluation of the interference of hemoglobin, bilirubin and lipids on Synchron LX-20 assays

Abstract: The influence of interference by hemolysis, icterus and lipemia on the results of routine chemistries may lead to wrong interpretations. The H-, I- and L-indices that can be measured by the Beckman LX-20 instrument (Beckman Coulter) in serum or plasma samples are a reliable semi-quantitative measure of the size of these interferences. A survey carried out in 16 Dutch clinical laboratories on the use of these indices demonstrated that in several of these laboratories, the influence of interferences is largely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 7 publications
1
24
1
8
Order By: Relevance
“…However, we have also demonstrated that more efforts should be placed on standardization of reporting of HI. In addition to previous concerns that have been raised regarding the sometimes arbitrary and lack of evidence-based cutoffs to define the limits at which clinically significant interference starts (16), all the instruments that we tested provide either quantitative or qualitative results that are roughly comparable, but which should always be linked to the instrument-specific alert value for each test in order to harmonize and streamline their effectiveness (Tables 3 and 4). It is also important to highlight that it is necessary to evaluate the influence of hemolysis for each test and to state the limits of acceptability for each, as proposed in some validation protocols (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…However, we have also demonstrated that more efforts should be placed on standardization of reporting of HI. In addition to previous concerns that have been raised regarding the sometimes arbitrary and lack of evidence-based cutoffs to define the limits at which clinically significant interference starts (16), all the instruments that we tested provide either quantitative or qualitative results that are roughly comparable, but which should always be linked to the instrument-specific alert value for each test in order to harmonize and streamline their effectiveness (Tables 3 and 4). It is also important to highlight that it is necessary to evaluate the influence of hemolysis for each test and to state the limits of acceptability for each, as proposed in some validation protocols (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In general, we followed the approach described in our investigation of interference on LX-20 assays. 6,7 For lipaemia we used the triglyceride concentration instead of the L-index, because Siemens describes in their instructions for use triglyceride concentrations up to 60 mmol/L, which are much higher than the concentration of about 12 mmol/L that matches the highest reported L-index of 10. The H-index in the sample with the highest haemoglobin concentration was about 10, the I-index in the sample with the highest bilirubin concentration was about 20 and the triglyceride concentration in the sample with the highest triglyceride concentration was about 60 mmol/L.…”
Section: Interference Studiesmentioning
confidence: 99%
“…Therefore, any simple solution for a complicated process is inappropriate. Moreover, the K + release by the erythrocyte is affected by a number of circumstances, reflecting different mechanisms, different populations and ultimately different results [1][2][3][4][5]. Other studies advocate that the H-index is useful for screening inadequate samples, justifying a new request for blood collection or even, providing an alert message for the clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Hemolysis is a major pre-analytical issue in current clinical pathology, prevalence can be as high as 3.3% of all routine samples, accounting for up to 40%-70% of all unsuitable specimens identified [1]. It may interfere in many lab tests, such as potassium, bilirubin, haptoglobin, liver enzymes, amylase, folic acid and iron [1][2][3][4][5]. Hemolysis is the main reason for the re-collection of blood samples, and so increasing TAT (turnaround time), costs on blood collection materials and other clinical products.…”
mentioning
confidence: 99%